2018
DOI: 10.1111/aphw.12131
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Health Implications of Students’ Friendship Formation during the Transition to University

Abstract: This study provides evidence for both (1) an indirect effect of friendship formation on self-reported health via perceived social support, and (2) a direct effect of friendship formation on a healthy diet. Broadly, these results highlight the importance of friendship formation and social integration for the long-term well-being of university students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 54 publications
2
8
0
2
Order By: Relevance
“…This supports previous research demonstrating the importance of friendships during the transition (e.g. Buote et al, 2007;Klaiber et al, 2018), whilst also highlighting the health benefits of social integration within university accommodation. In line with this, findings also revealed that participants who reported a low sense of belonging experienced higher levels of depression, anxiety, and loneliness.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This supports previous research demonstrating the importance of friendships during the transition (e.g. Buote et al, 2007;Klaiber et al, 2018), whilst also highlighting the health benefits of social integration within university accommodation. In line with this, findings also revealed that participants who reported a low sense of belonging experienced higher levels of depression, anxiety, and loneliness.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, the importance of developing new friendships during the transition period is well documented (e.g. Buote et al, 2007;Holton, 2017;Klaiber et al, 2018). New friendships play an important role in helping university students adjust to their new environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This idea is reflective of rich and interdisciplinary literature from fields such as epidemiology, psychology, and sociology, revealing the role of social and intimate relationships for a broad array of health outcomes and well‐being (e.g. Holt‐Lunstad et al., 2017; Klaiber et al, 2018; Pietromonaco & Collins, 2017; Tay et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Pitman et al, 2018), especially those who are students due to the occurrence of transitional stressors associated with starting of tertiary education (e.g. Dawson et al., 2019; Klaiber et al., 2018).…”
Section: Introductionmentioning
confidence: 99%